El Excentrico, 1974-07-20 - Garcia, Humberto:::Publisher::::::::::::; Garcia, Bert:::Manager::::::::::::; Garcia, Marc:::Editor:::::::::::: (San Jose, California; Garcia Printing, 2023)
July 20, 1974 [20 de julio de 1974]. No issue or volume number. Cover has photograph for the United Food Drive Dance at the Fiesta Latina Hall in San Jose, California.